2017
DOI: 10.1080/15563650.2017.1342828
|View full text |Cite
|
Sign up to set email alerts
|

Safety and effectiveness of physostigmine: a 10-year retrospective review

Abstract: In this retrospective cohort study, physostigmine administration to reverse anticholinergic delirium had a good safety profile, and often improved or resolved anticholinergic delirium when administered in doses less than 2 mg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 16 publications
2
33
0
2
Order By: Relevance
“…In this prospective observational study, we confirmed previously reported findings [8,[14][15][16][17] that physostigmine is effective in treating antimuscarinic delirium. Patients with antimuscarinic delirium that the CSPI recognized as one who would benefit from intervention and who were given physostigmine had improved delirium more often both by AMSS as well as by subjective report at two hours than those who were not, with an odds ratio of greater than 6.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In this prospective observational study, we confirmed previously reported findings [8,[14][15][16][17] that physostigmine is effective in treating antimuscarinic delirium. Patients with antimuscarinic delirium that the CSPI recognized as one who would benefit from intervention and who were given physostigmine had improved delirium more often both by AMSS as well as by subjective report at two hours than those who were not, with an odds ratio of greater than 6.…”
Section: Discussionsupporting
confidence: 90%
“…These findings resemble those of Rasimas et al [16], who found one arrhythmia each in the prospective and retrospective arms of their study, both thought not to be directly related to the administration of physostigmine. Similarly, Burns [14] reported one episode of bradycardia, while Arens et al [17] and Nguyen et al [18] reported no arrhythmias related to physostigmine administration in their cohorts.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations